Effects of Atypical Antipsychotic Treatment and Resistant Starch Supplementation on Gut Microbiome Composition in a Cohort of Patients with Bipolar Disorder or Schizophrenia - Flowers, Stephanie A; Baxter, Nielson T; Ward, Kristen M; Kraal, A Zarina; McInnis, Melvin G; Schmidt, Thomas M; Ellingrod, Vicki L (Pharmacotherapy, 2019)
Previous studies identified shifts in gut microbiota associated with atypical antipsychotic (AAP) treatment that may link AAPs to metabolic burden. Dietary prebiotics such as resistant starch may be beneficial in obesity and glucose regulation, but little is known mechanistically about their ability to modify gut microbiota in AAP-treated individuals. This investigation was undertaken to delineate mechanistically the effects of AAP treatment and resistant starch supplementation on gut microbiota in a psychiatric population. Cross-sectional cohort study. The study was performed in an outpatient setting. A total of 37 adults with a diagnosis of bipolar disorder or schizophrenia who were treated with an AAP (clozapine, olanzapine, risperidone, quetiapine, or ziprasidone [21 patients]) or lithium and/or lamotrigine (16 patients) for at least 6 months. Patients in the AAP group received raw unmodified potato starch (resistant starch) daily for 14 days. Of the 37 patients, the mean ± SD age was 52.2 ± 12.5 years, and 57% were male. The primary outcome was gut microbiome DNA composition. Microbiome DNA obtained from stool samples from all patients was subject to 16S ribosomal RNA (rRNA) gene sequencing before and during resistant starch supplementation. Inter- and intragroup microbial diversity measures were performed by permutational multivariate analysis of variance and the Inverse Simpson Diversity Index, respectively. Differentially abundant organisms were detected by using linear discriminant analysis effect size. Although no significant difference in overall microbiota composition was detected at baseline between AAP users and nonusers, non-AAP users showed increased fractional representation of Alistipes. AAP-treated women exhibited decreased diversity compared with non-AAP-treated women. Although the microbiome of AAP-treated patients varied with resistant starch administration, an increased abundance of the Actinobacteria phylum was observed. These data suggest that AAP treatment is associated with measurable differences in gut microbiota, particularly in female AAP-treated patients in whom reduced species richness was observed. Additionally, variable microbiome responses to resistant starch supplementation were seen, with a significant increase in starch degraders.